Consultation on fish genetic resources summary proceedings of a workshop convened by the International Center for Living Aquatic Resources Management (ICLARM) as part of the CGIAR System-wide Genetic Resources Programme (SGRP), 11-13 December 1995, Rome, Italy - Pullin, Roger S.V. (ed.); Casal, Christine Marie (ed.) (International Center for Living Aquatic Resources Management ; Rome CGIAR System-wide Genetic Resources Programme, 1996)
ICLARM conf. proc. ; 51